Preparation and Characterization of Functional Films Based on Chitosan and Corn Starch Incorporated Tea Polyphenols - Lepeng Gao (Coatings, 2021)
The functional films based on chitosan and corn starch incorporated tea polyphenols were developed through mixing the chitosan and starch solution and the powder of tea polyphenols by the casting method. The objective of this research was to investigate the effect of different concentrations of tea polyphenols on the functional properties of the films. Attenuated total reflectance Fourier transform infrared spectrometry and X-ray diffraction were used to investigate the potential interactions among chitosan, corn starch and tea polyphenols in the blend films. Physical properties of the blend films, including density, moisture content, opacity, color, water solubility and water swelling, as well as morphological characteristics, were measured. The results demonstrated that the incorporation of tea polyphenols caused the blend films to lead to a darker appearance. The water solubility of the blend film increased with the increase of tea polyphenol concentrations, while moisture content and swelling degree decreased. The hydrogen bonding between chitosan, starch and tea polyphenols restricted the movement of molecular chains and was helpful to the stability of the blend films. The results suggested that these biodegradable blend films could potentially be used as packaging films for the food and drug industries to extend the shelf life to maintain their quality and safety.